Kelesuan pandemik : hubungannya dengan pematuhan SOP, konflik kerjaya-keluarga, tekanan emosi dan risiko fizikal dalam kalangan masyarakat awam Malaysia - Siti Marziah Zakaria; Rusyda Helma Mohd; Fauziah Ibrahim; Norshaffika Izzaty Zaidey Nor; Mohd Nasir Selamat (Penerbit Universiti Kebangsaan Malaysia, 2021)
World Health Organization (WHO) has reported signs of pandemic fatigue among the global citizens, such as demotivation in abiding by the recommended protective behaviors due to misperception and ignorance. Consequently, the number of COVID-19 new cases is increasing globally. A systematic intervention strategy is highly required to avoid disruption in public healthcare services. Many countries in the world are facing this problem, including Malaysia. Malaysia’s healthcare system is at risk of collapsing following an upsurge in COVID-19 patients. Therefore, it is crucial to conduct a study to understand pandemic fatigue among Malaysians. This article aims to analyze the correlation between pandemic fatigue, compliance to SOP, emotional distress, work-family conflict, and physical risks. The study involved 2047 respondents from 14 states in Malaysia and it was designed as a cross-sectional survey. The findings indicated that there was no significant correlation between pandemic fatigue and compliance to SOP (r=. 07). However, there were positive correlations between pandemic fatigue and emotional distress (r=.65), work-family conflict (r =.66), and physical risk (r=.59) (p<.01). Although the finding has shown that the pandemic fatigue level was moderate, however, due to the extension of the Movement Control Order (MCO), there is a greater possibility that the pandemic fatigue level could increase. The Covid-19 vaccine is the most feasible initiative to combat the spread of the Covid-19 pandemic. Nevertheless, the community members must continue to practice SOP and comply with other government rules and directives.